Family Identification of Delirium in the Emergency Department in Patients With and Without Dementia: Validity of the Family Confusion Assessment Method (FAM‐CAM). Issue 5 (10th April 2020) - Mailhot, Tanya; Darling, Chad; Ela, Jillian; Malyuta, Yelena; Inouye, Sharon K.; Saczynski, Jane
Abstract : OBJECTIVE: To examine the ability of the family‐rated Family Confusion Assessment Method (FAM‐CAM) to identify delirium in the emergency department (ED) among patients with and without dementia, as compared to the reference‐standard Confusion Assessment Method (CAM). DESIGN: Validation study. SETTING: Urban academic ED. PARTICIPANTS: Dyads of ED patients, aged 70 years and older, and their family caregivers (N = 108 dyads). MEASUREMENTS: A trained reference standard interviewer performed a cognitive screen, delirium symptom assessment, and scored the CAM. The caregiver self‐administered the FAM‐CAM. Dementia was assessed using the Informant Questionnaire on Cognitive Decline in the Elderly and the medical record. For concurrent validity, performance of the FAM‐CAM was compared to the CAM. For predictive validity, clinical outcomes (ED visits, hospitalization, and mortality) over 6 months were compared in FAM‐CAM positive and negative patients, controlling for age, sex, comorbidity, and cognitive status. RESULTS: Among the 108 patients, 30 (28%) were CAM positive for delirium and 58 (54%) presented with dementia. The FAM‐CAM had a specificity of 83% and a negative predictive value of 83%. Most false negatives (n = 9 of 13, 69%) were due to caregivers not identifying the inattention criteria for delirium on the FAM‐CAM. In patients with dementia, sensitivity was higher than in patients without (61% vs 43%). In adjusted models, a hospitalization in the following 6 months was more than three times as likely in FAM‐CAM positive compared to negative patients (odds ratio = 3.4; 95% confidence interval = 1.2‐9.3). CONCLUSIONS: Among patients with and without dementia, the FAM‐CAM shows qualities that are important in the ED setting for identification of delirium. Using the FAM‐CAM as part of a systematic screening strategy for the ED, in which familiesʼ assessments could supplement healthcare professionalsʼ assessments, is promising. J Am Geriatr Soc 68:983–990, 2020 Abstract : See related editorial by Kennedy et al . in this issue.